2002
DOI: 10.1177/030908920202700201
|View full text |Cite
|
Sign up to set email alerts
|

The Philistines in the Bible: A Late-Monarchic Perspective

Abstract: The biblical references to the Philistines do not contain any memory of early Iron I events or cultural behaviour. A few texts, such as the Ark Narrative and stories reflecting the importance of Gath, seem to portray late Iron I and early Iron II memories. Most of the Philistine material, even if historically stratified and containing seeds of early tales as well as evidence for more than one redaction, is based on the geographical, historical and ideological background of late-monarchic times. Especially impo… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
5
0
1

Year Published

2010
2010
2019
2019

Publication Types

Select...
5
1

Relationship

1
5

Authors

Journals

citations
Cited by 32 publications
(8 citation statements)
references
References 61 publications
2
5
0
1
Order By: Relevance
“…30 Brandl in a lecture at an Oxford 2004 conference. 31 Mazar/Carmi (2001); Sharon (2001); this is in line with the initial, pre-radiocarbon low chronology proposal, which was based on archaeological and historical considerations - Finkelstein (1996). 32 Na'aman (1997b); Finkelstein/Piasetzky (2007a).…”
Section: Radiocarbon Resultssupporting
confidence: 58%
See 4 more Smart Citations
“…30 Brandl in a lecture at an Oxford 2004 conference. 31 Mazar/Carmi (2001); Sharon (2001); this is in line with the initial, pre-radiocarbon low chronology proposal, which was based on archaeological and historical considerations - Finkelstein (1996). 32 Na'aman (1997b); Finkelstein/Piasetzky (2007a).…”
Section: Radiocarbon Resultssupporting
confidence: 58%
“…22 Finkelstein et al (2007); the building identified by Eilat Mazar as the palace of King David will be dealt with below. 23 Finkelstein (2001); Ussishkin (2003). 24 Faust (2004).…”
Section: Why the Traditional Theory Was Wrongmentioning
confidence: 99%
See 3 more Smart Citations